The use of gelatine in wound ballistics research - Carr, Debra J.; Stevenson, Tom; Mahoney, Peter F. (Springer, 2018)
Blocks of gelatine are used in both lethality and survivability studies for broadly the same reason, i.e. comparison of ammunition effects using a material that it is assumed represents (some part of) the human body. The gelatine is used to visualise the temporary and permanent wound profiles; elements of which are recognised as providing a reasonable approximation to wounding in humans. One set of researchers aim to improve the lethality of the projectile, and the other to understand the effects of the projectile on the body to improve survivability. Research areas that use gelatine blocks are diverse and include ammunition designers, the medical and forensics communities and designers of ballistic protective equipment (including body armour). This paper aims to provide an overarching review of the use of gelatine for wound ballistics studies; it is not intended to provide an extensive review of wound ballistics as that already exists, e.g. Legal Med 23:21–29, 2016. Key messages are that test variables, projectile type (bullet, fragmentation), impact site on the body and intermediate layers (e.g. clothing, personal protective equipment (PPE)) can affect the resulting wound profiles.
Keywords: Gelatine Bullets; Temporary and permanent cavities; Lethality and survivability